Comorbidities of Gestational Diabetes Mellitus and Urinary Tract Infection: A Case Report - Dinda Aprilia; Eva Decroli; Alexander Kam; Robby Satria Putra (HM Publisher, 2023)
Background: Gestational diabetes mellitus (GDM) is defined as a condition of glucose intolerance that is found during pregnancy. In pregnant women, urinary tract infection (UTI) is one of the most common bacterial infections that can be found. The infection can be worsened by diabetes as it was shown that the risk of UTI in pregnant women with diabetes (27.6%) is higher than those without diabetes (3%-10.1%). This study aimed to present a case of gestational diabetes mellitus and urinary tract infection. Case presentation: A pregnant woman aged 38 years old with a 15-16 weeks gestational age was admitted with gestational diabetes mellitus and urinary tract infection. The patient was treated with an intravenous insulin drip and antibiotic. The patient was discharged after there was a clinical improvement. Conclusion: There are many risk factors that can contribute to the development of UTI in pregnant women, with one of those being inadequate glycemic control. The treatment of UTI in pregnant women with GDM is generally the same as in those without GDM.